Hard shell, soft blue-green core: Ecology, processes, and modern applications of calcification in terrestrial cyanobacteria - Patrick Jung; Laura Briegel-Williams; Stefan Dultz; Carina Neff; Gunnar Heibrock; Curtis Monger; Nicole Pietrasiak; Lena Keller; Julia Hale; Jan Friedek; Timo Schmidt; Georg Guggenberger; et al. (iScience)
Summary: Cyanobacteria are the oldest photoautotrophic lineage that release oxygen during photosynthesis, an ability that possibly evolved as far as 3.5 billion years ago and changed the Earth’s environment—both in water and on land. Linked to the mechanism of carbon accumulation by cyanobacteria during photosynthesis are their calcifying properties, a process of biologically mediated mineralization of CO2 by precipitation with calcium to CaCO3. In recent decades, scientific research has mainly focused on calcifying cyanobacteria from aquatic habitats, while their terrestrial relatives have been neglected. This review not only presents the ecology of terrestrial calcifying cyanobacteria in caves and biocrusts but also discusses recent biotechnological applications, such as the production of living building materials through microbial-induced carbonate precipitation for structural engineering, which has the potential to open a new and efficient pathway for mitigating climate change, e.g., as carbon capture and storage technology.